The classification and framing of religious dialogues in two English schools - Fancourt, N (Taylor and Francis, 2016)
This article explores the place of discourse about religions in education by comparing two very different schools. It initially outlines some of the current debates around religious discourse, notably in dialogue. A theoretical frame for analysing religious discourse in schools is proposed, combining a theorisation of three levels of dialogue with both notions of classification and framing, and a distinction between the formal curriculum and the institutional curriculum. Research in ‘Flintmead’ and ‘Headley’ is then described: the former an elite Anglican private boarding school, the latter a secular non-selective state day school. The analysis shows how the schools build complex structures across the different dialogical levels, between and within the formal and institutional curriculum, with varying strengths of classification and framing. In particular, similar approaches to religious education sit alongside different discursive structures. The implications of the study for further comparison are discussed, and for understandings of religious dialogue.